Prevalence of Pseudomonas aeruginosa and Acinetobacter baumannii at Baghdad hospital (Journal of the College of Basic Education, 2024)
Background: Both gram-positive and gram-negative bacteria are relevant to nosocomial infections according to many scientific inquiries. A. baumannii and P. aeruginosa are particularly significant contributors to nosocomial infections .the most common types of hospital-associated infections are surgical site infections, bloodstream infections. Objectives: to determine the frequency of A. baumannii and P. aeruginosa bacteria among Baghdad medical centers and their antibiotic susceptibility .Methodology: The incidence, clinical characteristics, antimicrobial susceptibility, and outcomes of nosocomial P. aeruginosa and A. baumannii at Baghdad Hospital lobbies and patients from Medical City in Baghdad, during a one-year period. Results: A total of 630 isolates of different bacterial types including (114) P. aeruginosa (221) A. baumannii, and others and different clinical specimens were collected between February 2023 to September 2023 from Hospital lobbies and patients from Medical City in Baghdad, Introductory identification of isolates is done through cultural identification, microscopic examination, and biochemical tests. also identified at the species level with the VITEK® 2 system by using ID GNB cards, and the results showed the highest percentages belonging to A. baumannii were in Children section was 61(33%), and P. aeruginosa were In patient samples was 31(20%). Conclusions: The incidence of nosocomial the percentages show that A. baumannii isolates more than P. aeruginosa in patients and in hospital lobbies, especially in Burn rooms units. The most active antimicrobial agents for P. aeruginosa were Meropenem (65%), and A. baumannii isolates were to Ceftriaxone (83%).